A Case of Possible Neurosarcoidosis Presenting as Intractable Headache and Panhypopituitarism. (6th August 2013) - Hwang, Jin Kyung; Cho, Joo Hee; Park, So Young; Son, Jung Il; Jo, Uk; Chin, Sang Ouk; Lee, Yun Jung; Choi, Moon Chan; Rhee, Sang Youl; Kim, Eui Jong; Chon, Suk
Abstract : Sarcoidosis is a chronic multisystemic inflammatory disease of unknown etiology, which is characterized by noncaseating granulomatous inflammation of the involved organs. It is known that neurosarcoidosis involving the nervous system occurs in about 5% of patients with sarcoidosis. However, neurosarcoidosis without systemic involvement is extremely rare. We present a case of suspicious neurosarcoidosis affecting the pituitary gland, which was manifested as chronic uncontrolled headache, panhypopituitarism, central diabetes insipidus, and hypercalcemia. Though the biopsy at the pituitary lesion was not performed due to the high risk of surgical complication, treatment was needed urgently and we started steroid therapy. After steroid therapy, we observed the immediate symptom relief with improved hypercalcemia. According to the follow-up examination, no recurrent symptom was seen, and resolution of the pituitary lesion with improving panhypopituitarism was noted.